Changes in Low-Value Services in Year 1 of the Medicare Pioneer Accountable Care Organization Program - Schwartz, Aaron L. (JAMA Intern Med, 2015)
IMPORTANCE: Wasteful practices are widespread in the US health care system. It is unclear if payment models intended to improve health care efficiency, such as the Medicare accountable care organization (ACO) programs, discourage the provision of low-value services. OBJECTIVE: To assess whether the first year of the Medicare Pioneer ACO program was associated with a reduction in use of low-value services. DESIGN, SETTING AND PARTICIPANTS: In a difference-in-differences analysis, we compared use of low-value services between Medicare fee-for-service beneficiaries attributed to provider groups that entered the Pioneer program (ACO group) and beneficiaries attributed to other providers (control group) before (2009–2011) vs. after (2012) Pioneer ACO contracts began. We adjusted comparisons for beneficiaries’ sociodemographic and clinical characteristics and for geography. We decomposed estimates according to service characteristics (clinical category, price, and sensitivity to patient preferences) and compared estimates between subgroups of ACOs with higher vs. lower baseline use of low-value services. MAIN OUTCOMES AND MEASURES: Use of, and spending on, 31 services in instances that provide minimal clinical benefit. RESULTS: During the pre-contract period, trends in use of low-value services were similar for the ACO and control groups. The first year of ACO contracts was associated with a differential reduction of 0.8 low-value services per 100 beneficiaries for the ACO group (95% CI: −1.2, −0.4; P<0.001), corresponding to a 1.9% reduction in service quantity (95% CI: −2.9%, −0.9%) and a 4.5% differential reduction in spending on low-value services (95% CI: −7.5%, −1.4%; P=0.004). Differential reductions were similar for services less vs. more sensitive to patient preferences and for higher- vs. lower-priced services. ACOs with higher than their markets average baseline levels of low-value service use experienced greater service reductions (−1.2 services per 100 beneficiaries, 95% CI: −1.7, −0.7; P<0.001) than ACOs with below average use (−0.2 services per 100 beneficiaries, 95% CI: −0.6, 0.2; P=0.41; P=0.003 for test of difference between subgroups). CONCLUSIONS AND RELEVANCE: During its first year, the Pioneer ACO program was associated with modest reductions in low-value services, with greater reductions for organizations providing more low-value care. ACO-like risk contracts may be able to discourage use of low-value services even without specifying services to target.